Pembentukan Kalimat Tanya Sebagai Sarana Komunikasi Verbal Dalam Bahasa Inggris Di Istana Maimon Medan - H Hidayati; Misla Geubrina; Muhammad Kiki Wardana (Jurnal TUNAS, 2021)
An interrogative sentence is a sentence that asks something or someone that is used to get a response, answer, or information from someone or about something. This training is an activity that is intended to provide understanding and ability to young people at the Maimon Palace tourist attraction to form and use interrogative sentences used in English. One of the verbal communication skills is expected to be used in daily life by the participants of this training activity, so that the knowledge gained from this training can be applied directly in various environments. The method used in this training is the lecture and question and answer method. This is done to facilitate the delivery of material and also interact with participants. The expected target of this training is that participants understand interrogative sentences, verbal communication and how to form interrogative sentences which are used as a means of verbal communication in English.